1992
DOI: 10.1182/blood.v79.3.798.bloodjournal793798
|View full text |Cite
|
Sign up to set email alerts
|

Rheological analysis of the adhesive interactions of red blood cells parasitized by Plasmodium falciparum

Abstract: Adhesion of parasitized red blood cells (RBCs) to vascular endothelium is thought to be a key factor in the pathology of falciparum malaria. However, quantitative analyses of the intercellular forces and of the effects of flow on adhesion have been lacking. We have characterized cytoadhesion of RBCs parasitized by the strains ITO4 (which can bind to receptors ICAM-1 or CD36) and FCR3A2 (which can bind to CD36 only) using micropipette manipulation and flow chamber techniques. Target cells were unfixed or glutar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…This value is comparable to the rosette binding strength of 440 ± 130 pN, as observed in one of the earlier studies (Nash et al, 1992b). In another study, average detachment forces of~100 pN were observed between iRBC and cultured endothelial cells lines expressing CD36 and ICAM-1 (Nash et al, 1992a). A more recent study quantifies the average adhesive forces between FCR3CSA late-stage iRBC and CSA-expressing CHO cells to be in the range of 100-200 pN (unpublished data).…”
Section: Discussionsupporting
confidence: 83%
“…This value is comparable to the rosette binding strength of 440 ± 130 pN, as observed in one of the earlier studies (Nash et al, 1992b). In another study, average detachment forces of~100 pN were observed between iRBC and cultured endothelial cells lines expressing CD36 and ICAM-1 (Nash et al, 1992a). A more recent study quantifies the average adhesive forces between FCR3CSA late-stage iRBC and CSA-expressing CHO cells to be in the range of 100-200 pN (unpublished data).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, PRBCs infected with the virulent parasite line could still adhere to both targets at stresses at which the avirulent line could not (0.4 Pa and greater). For Anderson parasites, the efficiency of adhesion (defined as the percentage of PRBCs that adhered during their passage through the flow chamber) at 0.1 Pa was approximately 1.5% and is similar to the efficiency previously measured for human RBC infected with P. falciparum (Nash et al, 1992). Once PRBCs had adhered, the interaction was strong ( Fig.…”
Section: Bovis-infectedsupporting
confidence: 84%
“…Adherence must be rapid enough to occur while the red cell is in the microcirculation, extensive enough to interrupt tissue perfusion, and strong enough to oppose reperfusion pressures (or shear forces) that will dislodge occlusive plugs. To better understand how flow and receptor-ligand pathways may regulate sickle cell adherence, a biophysical detachment assay [28][29][30] was utilized to study the quantity and strength of sickle erythrocyte adherence to endothelium as a function of flow conditions and adherence pathways. Ultimately, understanding the kinetics, strength, and level of adherence and detachment is important in defining the role of sickle erythrocyte adherence in initiating and propagating vasoocclusive complications.…”
Section: Introductionmentioning
confidence: 99%